Right time of phosphorus and zinc application to maize depends on nutrient–nutrient and nutrient–inoculum interactions. Issue 4 (4th July 2017) - Hussain, Shahid; Hussain, Muhammad Baqir; Gulzar, Aasim; Zafar-ul-Hye, Muhammad; Aon, Muhammad; Qaswar, Muhammad; Yaseen, Rizwan
ABSTRACT: Application of fertilizer at the right time is necessary for profitable yields. Phosphorus (P) and zinc (Zn) are important nutrients often found deficient in calcareous soils. Plant growth promoting rhizobacteria may increase availability of P and Zn from such soils. A pot experiment was conducted to compare the basal and late applications of Zn and P with or without rhizobacteria inoculation for improving fodder yield of maize ( Zea mays L.). The application times of Zn (5 mg kg –1 ) and P (30 mg kg –1 ) fertilizers to plants with or without rhizobacteria inoculation were (i) basal P + basal Zn, (ii) late P + basal Zn, (iii) basal P + late Zn, and (iv) late P + late Zn. Basal doses were applied at sowing and late applications were applied 30 days after. As compared to basal applications of both P and Zn, optimum fodder yields were achieved with basal P + late Zn without rhizobacteria inoculation, and with late P + basal Zn with rhizobacteria inoculation. Uptake of Zn and P, and root growth were also influenced by rhizobacteria inoculation and time of fertilizer application. This might relate with nutrient–nutrient and nutrient–inoculum interactions for a particular soil–crop combination. Therefore, the nutrients under consideration and rhizobacteria inoculation determines the right time of fertilizer application in maize.